Private Capital and Investment Climate for Economic Growth: Empirical Lessons based on ARDL bound test technique - Tchouassi, Gérard (European Journal of Sustainable Development, 2014)
<!--[if gte mso 9]> <![endif]--> Using time series, autoregressive distributed lags (ARDL)-bound test approach and error-correction model (ECM), this paper aims to analyze how private capital and investment climate contribute to economic growth in African countries: Cameroon, Côte d’Ivoire, Tunisia, South Africa and Zambia. We find that in short-run there is a significant relationship between private capital, economic freedom and economic growth in Cameroon, in Côte d’Ivoire, in South Africa and in Zambia. In long run, we establish that a long term relationship exists between the variables. This implies that there is a long run cointegration relationship among the variables in some equations in Cameroon, Côte d’Ivoire, South Africa and Zambia. Employing the appropriate order of the ARDL specification and multidimensional economic freedom proxies to examine this linkage, the results obtained are not all significant. JEL Classifications: C13, C22, E22, F43, O11, O47 Key-Words: Private capital, Investment climate, Economic freedom, Economic growth, Time series, ARDL bound test approach, Error-Correction Model. <!--[if gte mso 9]> Normal 0 14 false false false IT X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->